Jejepangan Having Fun: Tren dan Event Komunitas Cosplay di Jember - Edy Hariyadi; Heru SP Saputra; Didik Suharijadi; Agustina Dewi Setyari; Abu Bakar Ramadhan Muhammad (Mezurashii: Journal of Japanese Studies, 2025)
The development of interest in Japanese popular culture, especially cosplay and anime, among young people in Jember has shown a significant increase over time. This study aims to describe the development of cosplay culture in Jember and the factors that influence it. The research methods used are direct observation of cosplay events, interviews with cosplayers and event organizers, and analysis of cosplay community social media. Using Joseph Nye's soft power theory and Jean Baudrillard's hyperreality, this study found that the cosplay trend in Jember has become a medium for cultural expression and identity for young people, especially through various cosplay events and competitions held in shopping centers, tourist destinations, educational institutions, hotels, and cafes with events including Coswalk Competition, Cosplay Perform, JSong Competition, cover dance and sales of anime, manga, and game merchandise. The results of the study indicate the existence of hyperreality, namely cosplayers bringing to life the fictional characters they play, thus providing space for escapism and creativity. This study also found the role of cosplay as a form of Japanese cultural soft power that is accepted by the local community in Jember. Keywords: cosplay, Jember, Japanese popular culture, soft power, hiperreality